The role of environmental regulations and innovation in TFP convergence: Evidence from manufacturing SMEs in Viet Nam - Huu Thanh Tam Nguyen; Nguyen-Khac Minh; Tran-Nam Quoc (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This is a pioneer study investigating the relationship between environmental compliance and TFP convergence for SMEs. It examines the impacts of environmental compliance, and its combination with innovation, on TFP convergence of manufacturing SMEs. We applied the dynamic panel regression method to estimate stochastic TFP. We find evidence of a Ø-convergence but a σ-divergence. Impacts of environmental practices of firms - pollution abatement and control expenditure, and environmental treatment - are only significant through their interaction with innovation. The Ø-convergence in firms' TFP is influenced by their industrial identity, while firms' size and investment have marginal impacts
Keywords: D24; O3; Q55; 330; environmental practices; innovation; σ- and β-convergence; TFP stochastic